2020
DOI: 10.1021/acsapm.9b01051
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Responsive Multilayer Films of Micelle-Based Composites for Controlled Release of a Third-Generation EGFR Inhibitor

Abstract: Lung cancer is a complicated long-term disease, which is extremely difficult to cure. A traditional single drug delivery system cannot achieve desired long-term controlled release of therapeutic compounds. Our previous studies have found that temperature-responsive micelles demonstrated high loading efficiency and a long-term controlled release rate, which allows them to be an efficient drug delivery system. We utilized temperature-responsive micelles and hyaluronic acid biopolymers to create a sandwich-like m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…Primarily, the addition of adjuvants with a lower price or formulating composite NPs can boost the therapeutic efficiency [154]. Second, specific or sustained drug delivery and release can be exploited, such as microneedle methods, NP layered self-assembly, and controlled release of laden medicines maintained by nanoscale systems [155][156][157]. Improving formulations and procedures is also an efficient approach to lower production expenses.…”
Section: Lacunae In the Current Researchmentioning
confidence: 99%
“…Primarily, the addition of adjuvants with a lower price or formulating composite NPs can boost the therapeutic efficiency [154]. Second, specific or sustained drug delivery and release can be exploited, such as microneedle methods, NP layered self-assembly, and controlled release of laden medicines maintained by nanoscale systems [155][156][157]. Improving formulations and procedures is also an efficient approach to lower production expenses.…”
Section: Lacunae In the Current Researchmentioning
confidence: 99%
“…Recently, Jiang et al prepared pH-responsive (poly(methacrylic acid)/poly(alkyl methacrylate)) n (PMAA/PAMA) multilayers with tunable interfacial properties, 171 while Xu et al used block copolymer micelles (BCM) and hyaluronic acid (HA) biopolymers to develop temperature-responsive, hydrogen-bonded multilayers. 172 However, multilayers can also be salinity-responsive. Irigoyen et al reported that polyelectrolyte multilayers based on (PDADMAC/PSS) n assembled at 3 M NaCl can reduce their thickness of 46% at low ionic strength, offering interesting applications such as controlled barrier for saline streams.…”
Section: Polyelectrolyte Multilayers On Porous Substratesmentioning
confidence: 99%
“…Copper(I) complexes including diimine ligands with water-solubilizing groups have also been examined for their in vitro anticancer potential against human tumor cell lines, exhibiting moderate to high cytotoxic activities and with potential to overcome cisplatin resistant cell lines [17]. Other strategies employed to improve the delivery of chemotherapy include functionalization of the drug with ester or carboxylic acid moieties [18][19][20], assembling pH-or temperature-responsive multilayer polymers encapsulating drugs [21][22][23], and encapsulating drugs in nanosheets [24] or metal-organic frameworks [25].…”
Section: Introductionmentioning
confidence: 99%